Insulin Resistance and Acne: The Role of Metformin as Alternative Therapy in Men - Aikaterini Andreadi; Saverio Muscoli; Rojin Tajmir; Marco Meloni; Alessandro Minasi; Carolina Muscoli; Sara Ilari; Vincenzo Mollace; David Della Morte; Alfonso Bellia; Elena Campione; Nicola Di Daniele; et al. (Pharmaceuticals, 2022)
The association between acne and insulin resistance has not been investigated as thoroughly in males as it has been in women, despite the fact that in adult men, acne prevalence has grown. On the face, sebaceous glands produce and secrete sebum, which lubricates the skin and protects it from friction. Metformin, an insulin-sensitizing medication, may modify the association between acne vulgaris and insulin resistance (IR). Individuals with IR, metabolic syndrome or with impaired glucose tolerance are sometimes treated ‘off label’ with Metformin. In these conditions, IR may be a leading factor in the pathogenesis of acne, and in men, Metformin treatment may reduce the Global Acne Grading System (GAGS) score by enhancing insulin sensitivity. However, additional clinical studies are required to corroborate these assumptions.